Assessing respiratory inflammation among children living near to non-sanitary landfill using interleukin-6 (IL-6) - Syed Ismail, Sharifah Norkhadijah; Othman, Muhammad S.; Jamaluddin, Dora E.; Praveena, Sarva Mangala; Ho, Yu Bin; Zainal Abidin, Emilia; A. Wahab, Aini Syuhaida; A., Haryati (SCIENCEDOMAIN International, 2015)
Aims: To determine the respiratory inflammation among children living near to non-sanitary municipal solid waste landfill area and the concentration of Interleukin-6 cytokine. Study Design: A cross-sectional comparative study design. Place and Duration of Study: Sample: Pajam, Negeri Sembilan, Malaysia, between September 2013 and April 2014. Methodology: A total of 72 children were randomly selected based on the inclusive and exclusive criteria. A set of pre-tested questionnaires were utilized to obtain socio-demographic information and to predict health risk faced by the respondents. Saliva samples of the respondents were collected and analyzed using Human Interleukin-6 (IL-6) Platinum ELISA (Enzyme-Linked Immunosorbent Assay) kit. Results: The PM10 concentration for the exposed group was higher than the unexposed group with the mean ± standard deviation (SD) of 152.31±31.07 μg/m3 and 87.77±30.77 μg/m3 respectively. The mean ± SD of the Interleukin-6 for the exposed group was slightly higher than the unexposed group with the mean ± SD of 6.34±1.95 pg/ml and 5.77±1.08 pg/ml respectively. The most common symptoms reported was sneezing and sore throat. There was no significant correlation between PM10 concentration and IL-6 in this study. Conclusion: The findings exhibit that there was no association between Interleukin-6 and PM10 concentration of the respondent. However, there are likely potential adverse health impacts arising from particulates exposure among exposed children in this study. Respondents are advised to have a medical check-up in order to determine respiratory health status thus elimination the risks of acquiring respiratory inflammation.